1979
DOI: 10.1021/ja00498a008
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of drug-dinucleotide interactions. Empirical energy function calculations on the interaction of ethidium, 9-aminoacridine, and proflavin cations with the base-paired dinucleotides GpC and CpG

Abstract: Convergence for the /3-CI model conformer was obtained by constructing, at each cycle, not an extrapolated density matrix, but one representing 0.7 of the previous density matrix and 0.3 of the current density matrix. This is equivalent to applying a damping factor to the change in each array element of 0.3. ( 21) This anomeric energy may be an overestimate for the glycosyl chlorides, since it assumes that the CH3-0-CH2-CI torsion angle is unrestricted and 825 can have the optimum value of 74°. In a pyranose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(34 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…These showed that, in DNA as well as in RNA, intercalation into the pyrimidine-3' ,5'-purine sequence is 7 to 13 kcallmole more favorable than purine-3' ,5'-pyrimidine intercalation because base-intercalator overlap is more pronounced in the pyrimidine-(3'-5')-purine sequence than in the reversed one (1119). This intermolecular interaction is supported by intra molecular electrostatic forces rendering pyrimidine -3' ,5' -purine sequences more prone to intercalation (1115). In addition, stereochemically unfavorable interactions may playa role if the reversed base sequence is employed (1115,1117).…”
Section: Stereochemistry Of Intercalation Into Dna-and Rna-type Dinucmentioning
confidence: 99%
“…These showed that, in DNA as well as in RNA, intercalation into the pyrimidine-3' ,5'-purine sequence is 7 to 13 kcallmole more favorable than purine-3' ,5'-pyrimidine intercalation because base-intercalator overlap is more pronounced in the pyrimidine-(3'-5')-purine sequence than in the reversed one (1119). This intermolecular interaction is supported by intra molecular electrostatic forces rendering pyrimidine -3' ,5' -purine sequences more prone to intercalation (1115). In addition, stereochemically unfavorable interactions may playa role if the reversed base sequence is employed (1115,1117).…”
Section: Stereochemistry Of Intercalation Into Dna-and Rna-type Dinucmentioning
confidence: 99%
“…17,18 It exhibits distinctive mutagenic activity 19 ability to interact with DNA 22−28 and other biologically important molecules. 24,29,30 It also appears to be a convenient probe for investigating various physical features of biological systems. 31,32 Therefore, it is important to know whether simple derivatives of acridin-9-amine which have fixed structures of both tautomeric forms can be synthesized and investigated experimentally, and what impact the structure may have on their properties, including biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…This is so because a large number of studies, including significant theoretical contributions (17)(18)(19) …”
Section: Introductionmentioning
confidence: 99%